DESENVOLVIMENTO DE TECNOLOGIA SOCIAL SOBRE INFECÇÕES SEXUALMENTE TRANSMISSÍVEIS A PARTIR DO CONHECIMENTO E PERCEPÇÃO DE PUÉRPERAS - Nunes, Josi Barreto (2019)
Introduction: Sexually Transmitted Infections are caused by more than thirty etiological agents, are transmitted through sexual contact and, eventually, via blood, but can also happen from mother to child during pregnancy, childbirth or breastfeeding. Objectives: the scientific objectives were to identify the degree of knowledge of puerperal women in relation to Sexually Transmitted Infections, to correlate with clinical and sociodemographic data, as well as to understand their perceptions regarding health practices in prenatal care. The technological objective was to describe a social educational technology about Sexually Transmitted Infections. Method: the first manuscript emerged from a quantitative-qualitative, cross-sectional study, carried out in a large hospital in the interior of Rio Grande do Sul, from a structured interview with 230 mothers. Data collection took place between April and July 2019. The second manuscript describes the development of a social educational technology on Sexually Transmitted Infections, with strategies for digital media, offline media and audiovisual strategies. Ethical issues were respected, the study was approved by the Human Research Ethics Committee at Universidade Franciscana under CAAE 09626619.4.0000.5306. Results: The first manuscript identified that the majority of participants 54.8% were single, 75.4% were white, 82.6% had family income up to two minimum wages, 53% had high school education and 52.6% reported not having paid employment. The puerperal women answered a questionnaire, containing fourteen true and false questions, in order to assess knowledge about Sexually Transmitted Infections, the average score was 10.98 correct answers. The score variable was correlated with the other study variables and a significant difference was observed between the level of education and the questionnaire score. There was also a positive and weak correlation between the age and score variables. About educational practices 52.6% received some type of guidance on Sexually Transmitted Infections during prenatal care, 43.9% did not receive information. From the qualitative data, three categories emerged: Educational activity performed, Desired educational activity, and Effect of the desired educational activity. The second manuscript describes the products used in the dissertation, in the form of social technology entitled Mother of All as Questions: period of light for information on Sexually Transmitted Infections. Offline media, two health professionals, were authorized ambassadors of knowledge and were detained for spreading knowledge about Sexually Transmitted Infections in their health units, a board game about Sexually Transmitted Infections was also created, in order to use information in an available way ; digital media, accounts recorded on Facebook, 11 Instagram, e-mail, for the dissemination of topics; and audiovisual strategies, a fictional character was created, who recorded videos about Sexually Transmitted Infections, this material was published on the social networks used here. Conclusion: from the data collected, estimated as having some degree of knowledge about Sexually Transmitted Infections, and it was also possible to notice that individuals experience latent educational activities, or that discourages them as participants. The use of social technology in educational activities can be an ally for the prevention and treatment of Sexually Transmitted Infections, because it uses dynamic and attractive resources, with information transmitted in an objective way, it can captivate as participants and use knowledge exchange, allowing access of all.